Miscibility characteristics of poly (ethersulfone) (pes) hollow fiber membranes with charged-surface modifying macromolecules (csmm) for water separations applications - Bolong, Nurmin; Ismail, Ahmad Fauzi; Salim, Mohd. Razman; Matsuura, Takeshi (Penerbit UTM Press, 2008)
Investigation of the miscibility of the fabricated hollow fiber membranes containing polyethersulfone (PES), additives (water or Poly (vinylpyrrolidone) kollidone) and charged-Surface Modifying Macromolecules (cSMM) is elaborated. The fabricated hollow fiber membranes were successfully produced via phase inversion process using dry/wet spinning condition at extrusion rate at 2.5 cm3/min. It’s revealed that the attenuated total reflection Fourier transformed infrared (ATR-FTIR) has confirmed the blending of cSMMs in PES matrix by analyzing the shifts or intensity changes spectrum of the hollow fiber membranes. In addition, the glass transition (Tg) of the membranes determined via Differential Scanning Calorimetry (DSC) also confirmed the blending formation. The results proved the existence of charge modification which is important in enhancing the performance of nanofiltration membrane for water purification process.